2002
DOI: 10.1159/000052747
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic Arguments in Favour of a Taxonomic Revision of Lepilemur septentrionalis

Abstract: Cytogenetic investigations performed on 30 specimens of Lepilemur septentrionalis confirmed the existence of 4 karyotypes differing from each other by 1–2 chromosomal rearrangements. These data, pooled with those obtained in earlier studies, showed that out of 60 animals karyotyped only two kinds of hybrids were detected, allowing us to characterise two chromosomally polymorphic populations. No natural hybrids could be found between these two populations, which could thus be considered as two separate species.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 6 publications
0
19
0
1
Order By: Relevance
“…Ravaoarimanana et al 1999Ravaoarimanana et al , 2004Rumpler et al 2002). Groves (2005) and Mittermeier et al (2006), therefore, listed 8 species of sportive lemurs, all of them cytogenetically distinct Rumpler and Albignac 1978;Rumpler et al 2001;Thalmann and Ganzhorn 2003;). Since these publications, 3 molecular genetic studies (Andriaholinirina et al 2006a;Louis et al 2006b;Rabarivola et al 2006) have added a further 15 species, making it, with 23 species, the most diverse lemur genus.…”
Section: Family Cheirogaleidae Gray 1873mentioning
confidence: 99%
See 2 more Smart Citations
“…Ravaoarimanana et al 1999Ravaoarimanana et al , 2004Rumpler et al 2002). Groves (2005) and Mittermeier et al (2006), therefore, listed 8 species of sportive lemurs, all of them cytogenetically distinct Rumpler and Albignac 1978;Rumpler et al 2001;Thalmann and Ganzhorn 2003;). Since these publications, 3 molecular genetic studies (Andriaholinirina et al 2006a;Louis et al 2006b;Rabarivola et al 2006) have added a further 15 species, making it, with 23 species, the most diverse lemur genus.…”
Section: Family Cheirogaleidae Gray 1873mentioning
confidence: 99%
“…Forms occurring in both dry deciduous and humid forests that extend from Montagne d'Ambre southward to the Mahavavy River near Ambilobe and eastward at least as far as the Manambato River, and probably to the Fanambana River, north of Sambava, have been assigned to this taxon. The diploid chromosome number for the species ranges from 36 to 38 (Ravaoarimanana et al 2004;Rumpler et al 2001). Andriaholinirina et al (2006a) found that Lepilemur ankaranensis was more closely related to L. dorsalis than to L. septentrionalis.…”
Section: Family Cheirogaleidae Gray 1873mentioning
confidence: 99%
See 1 more Smart Citation
“…In 2001, Rumpler et al 38 concluded that the most northerly Lepilemur species, L. septentrionalis, already known to be karyotypically polymorphic, consisted of two reproductively incompatible but externally cryptic populations, both karyotypically heteromorphic and each with a distinctive mtDNA (cytochrome b) signature. One of the original subspecies populations, confined to the Sahafary forest to the east of the Montagne d'Ambre, was raised to species level as L. andrafiamenensis.…”
Section: Genus Lepilemurmentioning
confidence: 99%
“…All that can be said with certainty is that there is variation within Lepilemur and that much of this variation appears to be organized geographically. On the basis of the karyotypic and hybrid-recognition studies of Rumpler and his colleagues [38][39][40] it seems reasonable that most of the eight ''core'' taxa should provisionally be recognized at the species level. On the other hand, even quite large divergences in the cytochrome b gene seem to constitute rather weak evidence for speciation in the case of the three recently named species embedded within the ranges of L. ruficaudatus and L. dorsalis.…”
Section: Genus Lepilemurmentioning
confidence: 99%